Studi Kualitatif terhadap Perdagangan Ekspor dan Impor dalam Kerangka Ekonomi Syariah: Kajian Prinsip dan Praktik - Ahmad Latif Fachrezi; Madian Muhammad Muchlis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to explore the application of Sharia economic principles in export and import trade through a qualitative approach. Sharia principles such as the prohibition of riba, gharar, and maysir, as well as fairness and transparency in transactions, are examined in the context of international trade practices. Data were obtained through in-depth interviews with traders, Sharia practitioners, and financial experts. The results show that despite challenges such as riba-free financing and currency fluctuation risks, Sharia-based solutions like salam contracts, murabahah, and wa’ad methods can help overcome these obstacles. This study highlights the potential of Sharia economics in fostering more ethical and sustainable international trade. With the growing global interest in ethical trade, Sharia principles have the potential to play a significant role in the future of international commerce.